Loyalty in William Shakespeare's timon of Athens and pericles - Toh, Florence Haw Ching (2011)
The thesis undertakes the reading of master-servant relationship in two Shakespearean plays, Timon of Athens (1605) and Pericles (1607). While the growing body of secondary comments has focused on the plays’ protagonists, Timon and Pericles, the research devotes particular attention to two commonly neglected servant characters, the Steward and Helicanus. The introductory chapter of the thesis sets out to provide a background to the research. Chapter two offers a social background to the idea of servitude in Shakespeare’s Elizabethan England involving the ruling class and the servants as well as a literature review of the selected servant characters. The third chapter delves into the theoretical framework and methodology employed in carrying out the research. The argument of the thesis is augmented by utilizing Josiah Royce’s conceptions of loyalty, derived from his work The Philosophy of Loyalty (1908). By applying Royce’s concepts of loyalty to the selected servant characters, the thesis suggests that both the subservient characters displayed significant portrayals of loyalty in the plays which have been eminent in restoring and elevating their masters’ honour and dignity. In chapter four, the discussions involve the Steward’s loyalty in truth speaking, minimizing conflict and idealizing the lost cause which enhances his self-will and forgoes his self-gratification. Similarly for Helicanus, his loyalty assisted him in being truthful, sacrificial and non-judgmental which further allowed him to encourage social confidence, forgo self-gratification, promote unity and elevate his master. The thesis concludes with an emphasis on the pivotal role played by both the Steward and Helicanus in serving their respective masters. Through the instances and extent of loyalty examined in the thesis, it is hoped that the endeavour will instigate new textual interpretations, particularly in the area of Shakespearean studies.